DISTRIBUSI FONEM BAHASA MOR - Siti Masitha Iribaram (Balai Bahasa Provinsi Papua, 2019)
This study discussed about the phonemes distribution of Mor language. Mor language is one of the regional languages in Province of Papua that spoken by the community in the Moora Islands District, Nabire Regency. This research used descriptive method with three stages, namely data supply, data analysis, and presentation of data analysis result. Data analysis is performed after the data is classified. The analysis applied using the distribution method. The result of study showed that Mor language has 23 segmental phonemes consisting of sixteen consonants and seven vowel phonemes. The phonemes, namely/p/, /B/, /t/, /d/, /k/, /g/, /j/, /m/, /n/, /s/, /r/, /h/, /G/, /?/, /y/, /w/, /a/, /i/, /u/, /e/, /|/, /O/, and /E/. The phonemes of Mor language in the word are partially distributed complete and some are incompletely distributed. Phoneme/p/, /t/, /m/, /n/, /i/, /u/, /e/, /O/, /E/, and /a/ are complete distributed consonant. It means, those phonemes occupy all position in the word. The phonemes /B/, /k/, /g/, /j/, /s/, /r/, /h/, and /w/ are phonemes distributed only at the beginning and middle of words. The phonemes /?/, /G/, and /y/ are phonemes which distributed in the middle and the end of the words, while the phonemes /d/ and /|/ are phonemes distributed only at the middle of the words.